Family and population effects on disease resistance in a reptile. - Uller, T; Olsson, M; Madsen, T (2003)
Despite its importance in evolutionary biology, studies of the pattern of disease resistance in natural populations are rare. In this paper, we report patterns of infection of a viral eye disease in juvenile Swedish common lizards (Lacerta vivipara). Females were sampled at random from natural populations immediately prior to parturition with equal exposure of pathogens for all lizards once in captivity. No causative agents could be found that linked risk of disease to maternal/interfollicular transfer of pathogens. The results show that a major factor influencing offspring susceptibility is family identity, suggesting heritable variation in pathogen resistance. Our interpopulation comparison provides additional support for a link between genetics and disease resistance. Lizards in northern Sweden were not only more susceptible to the disease but were also more health compromised once infected, with relatively more reduced growth rate and increased mortality than lizards from the south. This scenario suggests that southern lizards have been under selection for resistance to this pathogen, whereas northern lizards have not, or at least not to the same degree. Thus, this study confirms the importance of genetic (family) effects on pathogen resistance with variation in this trait among natural populations.